2016
DOI: 10.1016/j.actatropica.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Association between Strongyloides stercoralis infection and cortisol secretion in alcoholic patients

Abstract: A higher prevalence of Strongyloides stercoralis infections has been reported in alcoholic patients compared to nonalcoholic patients living in the same area. Excessive alcohol consumption increases the levels of endogenous corticosteroids that subsequently enhance the fecundity of S. stercoralis parthenogenetic females. These corticosteroids also enhance the transformation of rhabditiform larvae into infective filariform larvae by mimicking the effect of the ecdysteroid hormones produced by the parasite, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 51 publications
3
22
0
6
Order By: Relevance
“…This action leads to the invasion of the intestinal mucosa, resembling the autoinfection mechanism observed in patients under massive corticosteroid therapy [73, 74]. In fact, we have recently observed that high endogenous cortisol levels in alcoholic patients may not be associated with susceptibility to S. stercoralis infection; however, once infected, this may lead to a high parasite load [37]. …”
Section: Immune Response To S Stercoralis and Immunity Alterationmentioning
confidence: 95%
See 1 more Smart Citation
“…This action leads to the invasion of the intestinal mucosa, resembling the autoinfection mechanism observed in patients under massive corticosteroid therapy [73, 74]. In fact, we have recently observed that high endogenous cortisol levels in alcoholic patients may not be associated with susceptibility to S. stercoralis infection; however, once infected, this may lead to a high parasite load [37]. …”
Section: Immune Response To S Stercoralis and Immunity Alterationmentioning
confidence: 95%
“…However, the rate of infection in the entire Costa Rica population was 0.1%, indicating that alcoholics were four to five times more susceptible to S. stercoralis infection [36], as observed in Brazilian studies. In fact, our group reported an occurrence of 23.5% of S. stercoralis infection in alcoholics from the Brazilian Northeast [37]. …”
Section: Epidemiology Of Strongyloidiasis and Association With Alcmentioning
confidence: 99%
“…Marques y cols., evaluaron 263 pacientes consumidores crónicos de alcohol, identificando una tasa de infección de 20,5% mientras en 590 individuos no alcohólicos, tan sólo 4,4% resultaron positivos 32 . En 2016, Silva y cols., identificaron resultados semejantes a los presentados en la literatura médica, observando una frecuencia de estrongiloidiasis entre individuos alcohólicos de 23,5% y entre no consumidores de alcohol de 5,4% 33 .…”
Section: Estrongiloidiasis Y Etilismounclassified
“…Alcoholism is considered a risk factor that compromises tissue repair by increasing susceptibility to infections and reducing the number of cells of the innate and adaptive immune systems [26,27]. Its consumption is also related to the formation of ROS, which induces cell morphological and functional destruction [28].…”
Section: Introductionmentioning
confidence: 99%